The Vision of a Digital Public Infrastructure for Agriculture - Dhulipala, Ram; Mehrotra, Nipun; Kanitkar, Ajit (Observer Research Foundation, 2024)
The book chapter is published on page no 105-121, by Ram Dhulipala, Nipun Mehrotra and Ajit Kanitkar. The authors published a policy brief in 2023 titled “The Vision of a Digital Public Infrastructure for Agriculture” for the T20/G20, which was subsequently selected out of 300+ briefs by the Government of India to be published as a detailed book chapter in 2024 in the G20 Compendium. The chapter emphasizes the dual challenge in agriculture of enhancing smallholder productivity and incomes while ensuring environmental sustainability. Digital technologies, when implemented responsibly, can address these issues by transforming agrifood systems. A conceptual approach termed "Digital Public Infrastructure for Agriculture" (DPI4A) focuses on equitable development in G20 nations, aligning with the IDEA framework from India. Key elements include ethical safeguards, public-private partnerships, and governance mechanisms. The chapter highlights G20 leadership in fostering partnerships, global pilots, and frameworks for collaboration to address climate change and equity challenges in agrifood systems.